2016
DOI: 10.2174/1574886310666150930113957
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile of Oral Iron Chelator Deferiprone in Chinese Children with Transfusion-Dependent Thalassaemia

Abstract: • Half of the identified ADRs related to deferiprone therapy occurred during the first three months of treatment. • A relatively high incidence of agranulocytosis and neutropenia. Hence close monitoring for white blood cell counts is advised in Chinese children under combined iron chelation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…1,8,9 Ethnic differences may influence the occurrence of agranulocytosis as reported in Chinese children on DFP. 10 Combined therapy was not associated with a higher risk for neutropenia consistent with existing data. 4 European sites reported neutropenia more often than non-European sites (13.5% vs.…”
Section: /9supporting
confidence: 84%
“…1,8,9 Ethnic differences may influence the occurrence of agranulocytosis as reported in Chinese children on DFP. 10 Combined therapy was not associated with a higher risk for neutropenia consistent with existing data. 4 European sites reported neutropenia more often than non-European sites (13.5% vs.…”
Section: /9supporting
confidence: 84%
“…Nonetheless, based upon a claimed ‘cardio-protective’ effect [2729], deferiprone is prescribed worldwide as first line therapy, either as monotherapy (15%), or in regimens combining deferiprone with less-than -therapeutic doses of other drugs (25%) [30, 31]. Deferiprone is frequently prescribed as first line therapy even to children (for example, 68.3% of children in the Middle East [32], despite inadequate monitoring [33–35]). Its recommendation in pediatric practice persists despite higher rates of toxicity in children, including neutropenia (12.6%), agranulocytosis (5%) [35], and liver dysfunction [36, 37]), than were reported in the Apotex-directed “safety” study [34].…”
Section: Discussionmentioning
confidence: 99%
“…Deferiprone is frequently prescribed as first line therapy even to children (for example, 68.3% of children in the Middle East [32], despite inadequate monitoring [33–35]). Its recommendation in pediatric practice persists despite higher rates of toxicity in children, including neutropenia (12.6%), agranulocytosis (5%) [35], and liver dysfunction [36, 37]), than were reported in the Apotex-directed “safety” study [34].…”
Section: Discussionmentioning
confidence: 99%
“…Other potential mechanisms are maturation arrest of granulocytic lineage or decreased production of granulocyte colony-forming units (98). Specific risk factors and pharmacogenetic dispositions have also not been identified yet (44,99). Our meta-analysis shows that the incidence of agranulocytosis in children and adolescents may be lower than the 0.5-0.9% reported previously (94,95).…”
Section: Deferiprone (Dfp)mentioning
confidence: 64%
“…neutropenia in the past for DFP or renal dysfunction for DFX). Furthermore, it was not always clear whether the patients were na€ ıve to iron chelation or switching from an (99,192,193) N, number of studied patients; PI, pooled incidence in per cent with 95% confidence interval; NR, not investigated and/or reported in any study publication. 1 Only one study reported this AE; if incidence is <0.001% only one decimal place is expressed (0.0%).…”
Section: Adverse Effects Reporting Qualitymentioning
confidence: 99%